UPACARA ADAT PERKAWINAN BENGKULU (Analisis Filosofis, Nilai Islam dan Kearifan Lokal) - Samsudin Samsudin (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2018)
The philosophical values  contained in the  building of the  traditional marriage of the  Malay community of the City of Bengkulu are a reflection of the socio-cultural relations of Malayness with Islamic values. Historically, Beng- kulu Malay Islam  was an incarnation of acculturation and  assimilation between Muslims who came  to Bengkulu. The position of the process of acculturation of Islam  in Bengkulu Malay society,  became very significant as the basis of the cultural process of Bengkulu society until now. Acculturation of values and internalization of Islamic values is very func- tional in shaping philosophical values in the custom of marriage of the Bengkulu community. This is expressed in every stage of the traditional marriage, there are ritual processions that are inter-related with local wisdom, Islamic values and other Islamic philosophical meanings.